2019
DOI: 10.1016/j.tws.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis and design of slender elliptical hollow sections in bending

Abstract: The local buckling behaviour and ultimate cross-sectional resistance of slender tubular elliptical profiles in bending are examined by means of numerical modelling. After successful validation of the numerical model against previous experimental results, a parametric study comprising 240 simulations was conducted in order to investigate the influence of cross-section aspect ratio, axis of bending, geometric imperfections and local slenderness on structural behaviour. The ultimate moments, moment-curvature rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Convergence studies, on similar elliptical hollow section specimens have been performed previously by Silvestre and Gardner [32] and McCann and Gardner [33]. In both studies, it was concluded that a characteristic mesh size of 10 ×10 mm can accurately simulate the behaviour of thin-walled EHS specimens, whilst optimizing computation time.…”
Section: Development Of Fe Modelsmentioning
confidence: 65%
“…Convergence studies, on similar elliptical hollow section specimens have been performed previously by Silvestre and Gardner [32] and McCann and Gardner [33]. In both studies, it was concluded that a characteristic mesh size of 10 ×10 mm can accurately simulate the behaviour of thin-walled EHS specimens, whilst optimizing computation time.…”
Section: Development Of Fe Modelsmentioning
confidence: 65%
“…( 10). Similar exercises have been conducted previously for hotrolled steel sections [41], stainless steel sections [42,45], concrete-filled steel elliptical hollow section beam-columns [46], slender steel elliptical hollow sections [47], reinforced-concrete structures [48,49], FRP laminates [50] and FRP-strengthened reinforced-concrete structural elements [51,52]; more detailed descriptions of the theoretical background to the methodology of these reliability analyses can be found in [45,48,53]. To the best of the author's knowledge, the reliability of structural elements containing particulate glass-polymer composites has not been assessed previously.…”
Section: Reliability Analysismentioning
confidence: 78%
“…The material over-strength of high strength steel was taken equal to 1.135 with a coefficient of variation COV of 0.055, while the COV of geometric properties was assumed equal to 0.02 [32]. For normal strength steel, the material over-strength of high strength steel was taken equal to 1.25 with a coefficient of variation COV of 0.055 [33]. The COV between the experimental and the numerical results, which was found equal to 0.025, was also considered.…”
Section: A Statistical Evaluation In the Fashion Of Annex D En 1990mentioning
confidence: 99%